Dynamics of personal social relationships in online social networks: A study on Twitter - Arnaboldi, V; Conti, M; Passarella, A; Dunbar, R (Association for Computing Machinery, 2013)
The growing popularity of Online Social Networks (OSN) is generating a large amount of communication records that can be easily accessed and analysed to study human social behaviour. This represents a unique opportunity to understand properties of social networks that were impossible to assess in the past. Although analyses on OSN conducted hitherto revealed some important global properties of the networks, there is still a lack of understanding of the mechanisms underpinning these properties, their relation to human behaviour, and their dynamic evolution over time. These aspects are clearly important to understand and characterise OSN and to identify the evolutionary strategy that favoured the diffusion of the use of online communications in our society. In this paper we analyse a data set of Twitter communication records, studying the dynamic processes that govern the maintenance of online social relationships. The results reveal that people in Twitter have highly dynamic social networks, with a large percentage of weak ties and high turnover. This suggests that this behaviour can be the product of an evolutionary strategy aimed at coping with the extremely challenging conditions imposed by our society, where dynamism seems to be the key to success. © 2013 ACM.